A combined physicochemical approach towards human tenocyte phenotype maintenance. (September 2021) - Ryan, C.N.M.; Pugliese, E.; Shologu, N.; Gaspar, D.; Rooney, P.; Islam, Md N.; O'Riordan, A.; Biggs, M.J.; Griffin, M.D.; Zeugolis, D.I.
Abstract: During in vitro culture, bereft of their optimal tissue context, tenocytes lose their phenotype and function. Considering that tenocytes in their native tissue milieu are exposed simultaneously to manifold signals, combination approaches (e.g. growth factor supplementation and mechanical stimulation) are continuously gaining pace to control cell fate during in vitro expansion, albeit with limited success due to the literally infinite number of possible permutations. In this work, we assessed the potential of scalable and potent physicochemical approaches that control cell fate (substrate stiffness, anisotropic surface topography, collagen type I coating) and enhance extracellular matrix deposition (macromolecular crowding) in maintaining human tenocyte phenotype in culture. Cell morphology was primarily responsive to surface topography. The tissue culture plastic induced the largest nuclei area, the lowest aspect ratio, and the highest focal adhesion kinase. Collagen type I coating increased cell number and metabolic activity. Cell viability was not affected by any of the variables assessed. Macromolecular crowding intensely enhanced and accelerated native extracellular matrix deposition, albeit not in an aligned fashion, even on the grooved substrates. Gene analysis at day 14 revealed that the 130 kPa grooved substrate without collagen type I coating and under macromolecular crowding conditions positively regulated human tenocyte phenotype. Collectively, this work illustrates the beneficial effects of combined physicochemical approaches in controlling cell fate during in vitro expansion. Graphical abstract: Image 1